Association of nuclear and mitochondrial genes with audiological examinations in Iranian patients with nonaminoglycoside antibiotics-induced hearing loss - Balali, M.; Kamalidehghan, B.; Farhadi, M.; Ahmadipour, F.; Ashkezari, M.D.; Hemami, M.R.; Arabzadeh, H.; Falah, M.; Meng, G.Y.; Houshmand, M. (Dove Medical Press, 2016)
Mitochondrial DNA mutations play an important role in causing sensorineural hearing loss. The purpose of this study was to determine the association of the mitochondrial genes RNR1, MT-TL1, and ND1 as well as the nuclear genes GJB2 and GJB6 with audiological examinations in nonfamilial Iranians with cochlear implants, using polymerase chain reaction, DNA sequencing, and RNA secondary structure analysis. We found that there were no novel mutations in the mitochondrial gene 12S rRNA (MT-RNR1) in patients with and without GJB2 mutation (GJB2+and GJB2-, respectively), but a total of six polymorphisms were found. No mutations were observed in tRNALeu(UUR) (MT-TL1). Furthermore, eight polymorphisms were found in the mitochondrial ND1 gene. Additionally, no mutations were observed in the nuclear GJB6 gene in patients in the GJB2- and GJB2+ groups. The speech intelligibility rating and category of auditory perception tests were statistically assessed in patients in the GJB2- and GJB2+ groups. The results indicated that there was a significant difference (P <0.05) between the categories of auditory perception score in the GJB2- group compared to that in the GJB2+group. Successful cochlear implantation was observed among individuals with GJB2 mutations (GJB2+) and mitochondrial polymorphisms compared to those without GJB2 mutations (GJB2-). In conclusion, the outcome of this study suggests that variation in the mitochondrial and nuclear genes may influence the penetrance of deafness. Therefore, further genetic and functional studies are required to help patients in making the best choice for cochlear implants.